The Stock Market Reaction to the Reserve Quantity Disclosures of U.S. Oil and Gas Producers* - SPEAR, NASSER A. (Contemporary Accounting Research, 1994)
Abstract. The purpose of this study is to examine the information content of the components of the annual change in the quantity of proved reserves reported by U.S oil and gas (O&G) producers. In particular, it investigates the contemporaneous association between the unexpected portions of discoveries, production, net purchases, and revisions of prior quantity estimates and unexpected security returns during the release week of the 1984 to 1988 annual reports or forms 10‐K of these firms. The empirical results suggest that (1) disaggregating the net change in the quantity of proved reserves into its components conveys additional information beyond that contained in the net change in total proved reserves itself, (2) discoveries are highly associated with security returns even after controlling for production, and (3) revisions, net purchases, and production have a modest influence on security returns. The findings of this study are interpreted within the context of the economic environment of the O&G industry during the test period. Résumé. L'auteur examine le contenu en information des éléments du changement annuel de la quantité de réserves prouvées dont font état les producteurs pétroliers et gaziers des États‐Unis. Il s'intéresse en particulier, pour la période 1984–1988, à l'association que l'on établit maintenant entre, d'une part, la portion inattendue des découvertes, la production, les achats nets et la révision des estimations antérieures de quantité et, d'autre part, les rendements imprévus des titres au cours de la semaine de publication des rapports annuels ou des formulaires 10‐K des entreprises. Les résultats empiriques donnent à penser que (1) la décomposition en ses différents éléments du changement net dans la quantité des réserves prouvées livre davantage d'information que le changement net global lui‐même, (2) les découvertes sont associées de très près aux rendements des titres, même une fois contrôlée la variable production, et (3) les révisions, les achats nets et la production ont une modeste influence sur les rendements des titres. Les résultats de cette étude sont interprétés dans le contexte économique du secteur pétrolier et gazier au cours de la période d'analyse.